2017
DOI: 10.15252/embj.201694781
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial chaperone HSP‐60 regulates anti‐bacterial immunity via p38 MAP kinase signaling

Abstract: Mitochondria play key roles in cellular immunity. How mitochondria contribute to organismal immunity remains poorly understood. Here, we show that HSP-60/HSPD1, a major mitochondrial chaperone, boosts anti-bacterial immunity through the up-regulation of p38 MAP kinase signaling. We first identify 16 evolutionarily conserved mitochondrial components that affect the immunity of against pathogenic (PA14). Among them, the mitochondrial chaperone HSP-60 is necessary and sufficient to increase resistance to PA14. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 88 publications
5
69
0
Order By: Relevance
“…In this study, we found that C. elegans starts to avoid the pathogenic bacterium P. aeruginosa within 30 min of exposure. This avoidance seems to be a very quick response compared to previous reports concerning avoidance of PA14, which is clearly observed from 8 to 16 hr after exposure (Hao et al, 2018;Jeong et al, 2017). Furthermore, we isolated a mutant defective in this quick avoidance behavior to PA14.…”
Section: Discussionsupporting
confidence: 45%
“…In this study, we found that C. elegans starts to avoid the pathogenic bacterium P. aeruginosa within 30 min of exposure. This avoidance seems to be a very quick response compared to previous reports concerning avoidance of PA14, which is clearly observed from 8 to 16 hr after exposure (Hao et al, 2018;Jeong et al, 2017). Furthermore, we isolated a mutant defective in this quick avoidance behavior to PA14.…”
Section: Discussionsupporting
confidence: 45%
“…Various microbes such as the opportunistic pathogen Pseudomonas aeruginosa can activate the UPR mt through the production of mitochondrial toxins (18,45). Consistent with a role in protecting the host from infection, ATFS-1 is required and sufficient for survival during P. aeruginosa infection (45,46). Interestingly, the mitochondrial chaperone HSP-60 that is transcriptionally up-regulated during the UPR mt by ATFS-1 (7, 10, 11) promotes host resistance during infection by enhancing the PMK-1/p38 MAPK innate immunity pathway through direct binding and stabilization of SEK-1/MAPK kinase 3 (46).…”
Section: Protection Against Pathogen Infectionmentioning
confidence: 97%
“…MAPK (Cell Signaling #4511), anti-Histone H3 (Cell Signaling #9715), anti-alpha tubulin (abcam ab40742). phospho-PMK-1 western blot assays were performed as described in 71 .…”
Section: Immunoblottingmentioning
confidence: 99%